2018
DOI: 10.1016/j.marpolbul.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal trends and body size differences of OCPs and PCBs in Laeonereis culveri (Polychaeta: Nereididae) from Southwest Atlantic estuaries

Abstract: Southwest Atlantic (SWA) estuaries have been historically impacted by industrial and agricultural activities that represent an important source of organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs). Intraspecific differences in OCPs and PCBs levels were evaluated in the benthic polychaete Laeonereis culveri from SWA estuaries (Samborombón; Mar Chiquita; Quequén Grande and Bahía Blanca) at different spatio-temporal scales. Regarding inter-and intra-estuarine spatial comparisons polychaetes sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Recently, it has been shown that human pressures might help to predict current geographic range sizes [47] and that the high degree of human modification of natural ecosystems has primarily impacted the speciesenvironment relationship [39] For instance, the mammalian body mass is lower closer to human settlements or in recently converted agricultural areas. Hence, it is likely that temporal and spatial dynamics of functional traits are also being affected by contamination [48,49].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Recently, it has been shown that human pressures might help to predict current geographic range sizes [47] and that the high degree of human modification of natural ecosystems has primarily impacted the speciesenvironment relationship [39] For instance, the mammalian body mass is lower closer to human settlements or in recently converted agricultural areas. Hence, it is likely that temporal and spatial dynamics of functional traits are also being affected by contamination [48,49].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Diaz-Jaramillo M assessed nonspecific differences in OCP and PCB levels at different scales in the benthic polychaete Laeonereis culveri from SWA rivers. Concentrations of OCPs/PCBs were associated with animal body weight, but this covariate was not associated with the observed differences [3]. Therefore, in a long period of time in the future, how to determine the optimal development model and realize the coordinated development of economy and environment is a major problem that needs to be solved in future development [4][5].…”
mentioning
confidence: 99%